Efficacy and safety of sedation during endoscopic submucosal dissection of gastric cancers using a comparative trial of propofol versus midazolam - Kikuchi, Hitomi; Hikichi, Takuto; Watanabe, Ko; Nakamura, Jun; Takagi, Tadayuki; Suzuki, Rei; Sugimoto, Mitsuru; Waragai, Yuichi; Konno, Naoki; Asama, Hiroyuki; Takasumi, Mika; Sato, Yuki; Obara, Katsutoshi; Ohira, Hiromasa (Endoscopy International Open, 2018)
Background and study aims Proper sedation is necessary for the safe and satisfactory completion of endoscopic submucosal dissection (ESD) for early gastric cancer. This study was conducted as a comparative trial of efficacy and safety, comparing propofol-based sedation and midazolam-based sedation during ESD of early gastric cancer patients.Patients and methods This study examined 64 lesions in 58 patients treated using ESD with midazolam plus pentazocine between July 2013 and January 2014 (group M) and 237 lesions in 216 patients treated by ESD using propofol plus pentazocine between February 2014 and December 2015 (group P). The two groups were compared in terms of the frequency of body movement during ESD as the primary outcome and in terms of the procedure time, en bloc resection rate, intraoperative change in cardiorespiratory dynamics, and postoperative awareness as the secondary outcomes. Body movement was defined as movement by a patient that required interruption of the procedure or restraint of the patient’s body trunk, and addition of a sedative agent.Results The median frequency of body movement during ESD was significantly lower in group P (0 times) than in group M (3 times) (P < 0.001). No significant difference was found for the mean procedure time (117 min in group P; 127 min in group M). Although no significant difference was found in the incidence of hypoxemia, bradycardia, or bradypnea, the incidence of hypotension was significantly higher in group P (31.5 %) than in group M (6.9 %) (P = 0.004). Patients in group P had significantly higher postoperative awareness immediately after ESD and at 1 hour after ESD (P = 0.002 and 0.022, respectively).Conclusion These results demonstrate the efficacy and safety of propofol-based sedation for gastric ESD.